Accurate determination of polarization fields in (0 0 0 1) c-plane InAlN/GaN heterostructures with capacitance-voltage-measurements. (11th October 2018) - Susilo, Norman; Roumeliotis, Georgios G; Narodovitch, Michael; Witzigmann, Bernd; Rychetsky, Monir; Neugebauer, Silvio; Guttmann, Martin; Enslin, Johannes; Dadgar, Armin; Niermann, Tore; Wernicke, Tim; Strittmatter, André; et al.
Abstract: In this paper the internal electric fields of nearly lattice matched InAlN/GaN heterostructures were determined. Pin -diodes containing InAlN/GaN heterostructures grown on sapphire substrates by metalorganic vapour phase epitaxy were fabricated by standard lithography and metallization techniques. To determine the polarization fields in the InAlN quantum wells capacitance-voltage-measurements were performed on the pin -diodes. To reduce the measurement error, the heterostructure thicknesses were accurately determined by transmission electron microscopy. Large polarization fields, which correspond mainly to the spontaneous polarizations, for In0.15 Al0.85 N ( MV cm −1 ), In0.18 Al0.82 N ( MV cm −1 ) and In0.21 Al0.79 N ( MV cm −1 ) quantum wells were observed. The results of the internal field strength and field direction are in excellent agreement with values predicted by theory and a CVM-based coupled Poisson/carrier transport simulation approach.